(untitled) (Transport systems and technologies, 2020)
This article analyzes the existing technology in organizing short-distance runs and offers proposals for improving the planning of rolling stock routes in order to reduce operating costs and distribute the freight operation between different modes of transport. The expediency in prediction calculations of the freight operation volume on the formation of reliable daily planning has been researched. The rationality of railway transportation, which is more expedient to carry out by other modes of transport, is determined by technical and economic calculations or pre-established areas for the rational use of different transport modes. The most typical irrational transportation is short-distance runs. Cargo transportation in cars at a distance of 30-50 km, sometimes more is considered as short-distance one. These transportations are more efficient to carry out by road. Transportations by railways are also irrational during the navigation period in parallel by waterways. In certain areas, it is economically more profitable to use mixed rail-water transportation. It is important to take into account the peculiarities of short-distance runs and when determining the cost of transportation to balance the level of freight tariffs. Thus, reducing the length of short-distance runs has a significant impact on the cost of transportation. In order to reduce these distances, there are several options: replace these transportations by road, if it is possible, or to rationalize the planning of rolling stock routes and distribute the cargo in such a way as to consistently collect it from the warehouses, without unnecessary runs to the warehouses.